2015
DOI: 10.1038/nrendo.2015.138
|View full text |Cite
|
Sign up to set email alerts
|

Paget's disease of bone—genetic and environmental factors

Abstract: Paget's disease of bone is generally diagnosed in individuals aged >50 years, usually manifests in one or several bones and is initiated by osteoclast-induced osteolytic lesions. Subsequently, over a period of many years, osteoblastic activity can result in sclerosis and deformation of bone. The prevalence of Paget's disease is highest in the UK and in countries where a large number of residents have ancestors from the UK. Currently, in many countries, the prevalence of the disorder has decreased. A considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 114 publications
(120 reference statements)
0
32
0
2
Order By: Relevance
“…P62 gene mutation was considered to be the main cause of Paget's disease of bone (PDB) [25] , [26] , [27] , [28] , which is a skeletal disorder characterized by osteolytic lesions and overactive osteoclasts. To date, 28 distinct P62 mutations have been reported in PDB patients and the most commonly identified mutation leads to a proline to leucine substitution at residue 392 (P392L) [28] , [68] . Dysregulated expression of P62 protein promotes osteoclastogenesis, bone resorption and osteolytic lesions through the NF-κB activation pathway, leading to focal areas of aberrant and excessive bone turnover of PDB patients [69] .…”
Section: The Role Of P62 In Osteoclastogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…P62 gene mutation was considered to be the main cause of Paget's disease of bone (PDB) [25] , [26] , [27] , [28] , which is a skeletal disorder characterized by osteolytic lesions and overactive osteoclasts. To date, 28 distinct P62 mutations have been reported in PDB patients and the most commonly identified mutation leads to a proline to leucine substitution at residue 392 (P392L) [28] , [68] . Dysregulated expression of P62 protein promotes osteoclastogenesis, bone resorption and osteolytic lesions through the NF-κB activation pathway, leading to focal areas of aberrant and excessive bone turnover of PDB patients [69] .…”
Section: The Role Of P62 In Osteoclastogenesismentioning
confidence: 99%
“…The dysregulated expression of the P62 protein promotes osteoclastogenesis, bone resorption and osteolytic lesions. Therefore, P62 has long been thought of as a promising molecular target in PDB and other bone metabolic diseases [28] .…”
Section: Introductionmentioning
confidence: 99%
“…Although still controversial, some consider paramyxovirus infection, especially measles virus infection, to be a potential risk factor in PDB development. 9, 10, 11 Recently, a marked decline in the prevalence of PDB in some regions has been noted, a finding that suggests a role for environmental factors in PDB development. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, animal-related factors may be important in the etiology of PDB and may interact with SQSTM1 mutations, thus influencing the disease severity [40]. It was reported that the decreasing incidence of Paget's disease, which could be attributed to measles vaccination, supports an etiologic role of the virus [41]. However, RNA of the measles virus was not found in the bone marrow and bone cell cultures isolated from patients with Paget's disease in New Zealand [42].…”
Section: Discussionmentioning
confidence: 99%